Thermal engineering a textbook of practicals - Kumar, P.V. Ram (Alpha Science, 2011)
Consists of Practicals in Thermal Engineering, I C Engines and Heat Transfer. Suitable for BE Mechanical Engineering students, this book covers three semesters of the course. It also includes a chapter that intends to help students to understand the basic fundamentals of thermal engineering